Semantic Web Evaluation Challenges : SemWebEval 2015 at ESWC 2015, Portorož, Slovenia, May 31 - June 4, 2015, Revised Selected Papers /: SemWebEval 2015 at ESWC 2015, Portorož, Slovenia, May 31 - June 4, 2015, Revised Selected Papers. (2015) - Unknown
No abstract available